2013
DOI: 10.1111/ajo.12135
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal outcomes following peripartum hysterectomy from a single tertiary centre

Abstract: Peripartum hysterectomy is a major procedure carrying a high morbidity rate. In this series, maternal survival was 100%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The association between (previous) cesarean delivery and hysterectomy is consistent with previous studies. 109,132,139 Clinical outcomes in these women may be better, because blood products and experienced staff could be more readily available. Many of these are not detected before delivery, so that hysterectomy could not be anticipated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between (previous) cesarean delivery and hysterectomy is consistent with previous studies. 109,132,139 Clinical outcomes in these women may be better, because blood products and experienced staff could be more readily available. Many of these are not detected before delivery, so that hysterectomy could not be anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Interstudy heterogeneity was assessed using x 2 test for heterogeneity. 1,[4][5][6]9,10,[91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110] Two studies were analyzed as one (same sample), 4,113 so the total number of papers was considered 128. Pooled odds ratio (OR) with 95% CI was calculated for categorical variables.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, symptoms of hypovolemic shock were observed in 11 (21.25) women. Eight (15.4%) subjects required ICU admission, while other authors reported the following rates: 43.0% (Jagielska et al), and 57.4% (Jones et al) [14,23].…”
Section: Discussionmentioning
confidence: 94%
“…Data about other countries include 0.024% for Denmark, 0.041% for UK, and 0.146% for the Czech Republic [13][14][15]. In the developing countries, with low socio-economic status, the rate of obstetric hysterectomy is several times higher.…”
Section: Discussionmentioning
confidence: 99%